Teotl, Cipactly and the theosophical intelligentsia of El Salvador - Mejía Burgos, Otto German (2022)
In order to understand the development of Theosophy in El Salvador, this paper is divided into three sections The first deals with the history of the oldest lodge in the country, which still exists today, the "Teotl Theosophical Society", the second analyzes, Cipactly, a magazine that published a series of articles on the doctrine under study during the 1930s. Finally, the last section outlines the trajectory of some of the most outstanding intellectuals of the early twentieth century who were members of the lodges or who simply sympathized with the movement.